(untitled) (Proceedings of Southern Federal University. Philology, 2015)
The article analyzes the methods of organization of chronotopic Nodes in “narration in measured terms” “The Red Wheel” by A.I. Solzhenitsyn. It highlights the relevance to the modern Solzhenitsyn study that is seen undifferentiated in studies devoted to Alexander Solzhenitsyn in the work of the principle of Node as a moment of conceptualization stories writer and method of nodal points as the main form of artistic thinking. Differentiating, following M.M. Bakhtin, architectonic and compositional forms, the author argues that the principle of Node in its relation to the principle of the cyclization is purely a compositional form of organization of verbal masses; it is carried out in the aesthetic object architectonic form of artistic completion of the historical events in the author’s historiosophical concept; historiosophical in terms of its conceptually included aesthetic object, unlike composite molding unit. By analyzing the types of chronotopes operating in each of the four nodes the work is approved by the fact that, using traditional types of chronotopes, but composing them in a special, unconventional way, and sometimes transforming them, Solzhenitsyn is based on the author’s own time-space, laying the foundations of a new correlative couples architectonic and compositional forms, which found its expression in the principle of Node. Keywords: principle of node point, method, author’s time-space, chrono- tope works, architectonic form, compositional form, historiosophical concept. Kalashnikova Svetlana Mikhailovna - candidate of linguistics, professor assistant, Russian literature dpt. Institute of philology, journalism and cross-cultural communication. Southern federal university. Phone: 8-928-151-12-38;